Curriculum Development for the Subject of “Jadi Pendamping Adik” in Grade X of Senior High School - Sera, Marianus A.G; Situmorang, Robinson; Siregar, Eveline (Journal of Education Reseach and Evaluation, 2021)
The curriculum is one component of education that has an important role in determining the quality of education. Therefore, curriculum development is very important. This study aims to develop a curriculum for the subject of "Jadi Pendamping Adik" in grade X of Senior High School. This study was a research and development (RnD) that uses the Dick and Carrey model as a curriculum development procedure. The steps of curriculum development namely: identifying learning objectives/learning outcomes; conducting learning analysis; analyzing student characteristics and learning contexts; writing specific learning objectives; developing assessment instruments; developing learning strategies; selecting and developing teaching materials; conducting formative evaluations and revisions. Data were collected by an instrument in the form of an expert assessment questionnaire. Analysis of the feasibility of data from experts using qualitative and quantitative descriptive data analysis. The results of the feasibility analysis from learning design experts, the percentage of achievement level is 92.5% with very good qualifications and is suitable for use with revisions as needed. The results of the feasibility analysis from each material expert are 90% and 92.5% with very good qualifications and are suitable for use with revisions as needed. The development of the curriculum for the subject of "Jadi Pendamping Adik" in grade X of Senior High School is worthy of being used as a guide in learning. Based on the feasibility assessment by instructional design expert and material expert, the development of a curriculum is suitable for learning in the hope that it can improve the quality of learning.